How does Legalization alter Islamists’ Electoral Strategies? A Comparative Study of Mauritania’s Tawassoul Party in the 2006 and 2013 Local Elections - Matt Buehler (L’Année du Maghreb)
This study examines the Islamist political party in Mauritania, the National Rally for Reform and Development (Tawassoul) which ran candidates in the local elections of 2006 and 2013, respectively, both as a banned party and unbanned party (after legalization in 2007). Drawing on original data collected during fieldwork in Mauritania, and also using Arabic interviews with Tawassoul politicians, this study compares variation in Islamists’ electoral strategies during their period of illegality compared with their period of legality. As a banned party competing in 2006, Mauritania’s Islamists focused on running candidates in districts of their traditional supporters, urban and religious voters. However, after the Islamist party gained legalization, its candidates for the 2013 elections concentrated less exclusively on urban areas, becoming statistically neither more nor less likely to compete in urban districts than rural ones. Moreover, Islamists candidates became statistically more likely to try to gain a brand-new, unprecedented political foothold in rural districts. This study concludes by positing a potential explanation, focusing on the party’s desire to attract support from marginalized social groups based in rural areas, especially Haratine voters.